The third-space professional: a reflective case study on maintaining relationships within a complex higher education institution. Issue 1 (2nd January 2017) - Stoltenkamp, Juliet; van de Heyde, Valentino; Siebrits, André
Abstract: This paper showcases the work of Third Space professionals in a complex higher education (HE) setting, and specifically its impact on the building of trust relationships and innovative approaches. It makes use of a case-study methodological approach, reflecting on the experiences of various stakeholders within pilot phases. The findings reveal challenges related to maintaining trust relationships, which can be threatened by technicist approaches. The reflective case study explores an innovative live-streaming project and the related pedagogical approaches by Instructional Design experts, as Third Space professionals, who have carved out a critical space within a HE setting. This investigation, and its related lessons, highlights that learning-and-teaching aspects, training and support, reconciliation of trust relationships, can be applied to Third Space professionals in other HE institutions.